Impact of Temperature on Biological Denitrification Process - Amatya, Iswar Man; Kansakar, Bhagwan Ratna; Tare, Vinod; Fiksdal, Liv (Journal of the Institute of Engineering, 2009)
Nitrate removal in groundwater was carried out by biological method of denitrification process. The denitrification and without denitrification were performed in two different sets of reactors. Each reactor consists of two columns connected in series packed with over burnt bricks as media. The filtration rate varied from 5.3 to 52.6 m/day for denitrification process. The ammonia, nitrate and nitrite nitrogen concentrations were measured at inlet, intermediate ports and outlet. The temperature varied from 10 to 30°C at 2°C intervals. The results demonstrated that high amount of nitrate nitrogen removed in groundwater at denitrification process. The nitrate nitrogen removed by denitrification varied from 3.50 to 39.08 gm/m3/h at influent concentration from 6.32 to 111.04 gm/m3/h. Denitrification was found more significant above 16°C. Key words: Over burnt brick, Denitrification, Filtration rate and Temperature Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp. 121-126 doi: 10.3126/jie.v7i1.2070